A stability-indicating LC method for difloxacin in the presence of degradation products - Cazedey, Edith Cristina Laignier; Juodinis, Vanessa D'amaro [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
A novel stability-indicating reversed-phase liquid chromatographic (LC) method for the determination of difloxacin (DI) in coated tablets in the presence of degradation products is described. The method was developed using isocratic mode on a reversed-phase C18 column (250 x 4.6 mm id, 5 Î¼m particle size). The mobile phase containing a mixture of 5% acetic acid-methanol (70: 30, v/v) was pumped at a constant flow rate of 1.0 mL/min. The eluted compounds were monitored at 276 nm. DI was subjected to the stress conditions of oxidative, acid, base, hydrolytic, thermal and photolytic degradation. DI was found to degrade significantly in oxidative, acid and base degradation conditions and mildly in hydrolytic degradation conditions and stable in thermal and photolytic degradation conditions. All degradation products were well resolved from the main peak providing the stability-indicating power of the method. The developed method was validated as per International Conference on Harmonization (ICH) guidelines with respect to specificity, limit of detection, limit of quantitation, precision, linearity, accuracy, robustness and system suitability.
Keywords: Liquid chromatography; Difloxacin; Stability-indicating method; Pharmaceutical analysis; Validation